Como conservar uma coleção "sobre rodas": as coleções do Museu Nacional dos Coches : testemunho de uma mudança - Dargent, Ana Rita Ezequiel (2020)
The construction of a new Museu Nacional dos Coches, Belem, in January 2013, and the subsequent transfer and instillation of all museum content, has created new challenges and renewed ways of looking at the vast potential of all assets as well as encouraged countless initiatives in the areas of conservation, study and communication of the different collections. As commonly happens when preparing a change, enthusiasm connected to “starting anew” and trying to do better were strongly felt. A closer look at questions concerning the Museum’s history, in particular questions related to the foundress Queen, D. Amélia’s, life experiences and the history of the collections, was both necessary and essential in order to obtain a more clarified understanding of the various nuclei. It consequently generated the motivation for a new investigation based on documental sources and direct observation which would allow for a more assertive and validated analysis of the physical condition of the assets themselves. This complex logistical journey, managing and organizing the collections, was supported by the available human and financial resources and created new strategies, procedures and operational methods which should be analysed, correlated, and gathered for future memory. The singular character of this patrimony, its undeniable historical significance, and the great prestige obtained among visitors as well as national and international investigators would certainly maintain the position of this Museum as the most visited among all national museums. With this study we intend to offer the public a new point of interest in these peculiar assets, most of which are installed on wheels. At the same time, we are confident that we can stimulate the imagination, bring back distant memories and turn important data about collection management, often left inside institutional and scientific limits, public. We hope to contribute to the developing studies and preservation of Museu Nacional dos Coches’ collections. We also hope that these facts serve as a guideline for emphasizing the importance of the preservation of this heritage, which is recognized all over the world, and help build multidisciplinary teams with specialized knowledge concerning maintenance and preservation of all different collections in the future.